2019
DOI: 10.1080/09744053.2019.1635416
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Ghana’s cocoa sector through environmentally smart agricultural practices: an assessment of the environmental impacts of cocoa production in Ghana

Abstract: The sustainability of the cocoa industry in the developing world depends heavily on the preservation of the natural environment. There is, therefore, an urgent need for more research, policies and strategies that will help address and minimize the environmental impacts of cocoa production. This study was conducted using both secondary and primary data sources. The secondary data were collected from documentary sources such as reports from the Ministry of Food and Agriculture and the Cocoa Pests and Diseases Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, substituting the use of inorganic fertiliser with organic fertiliser would decrease the emissions and their related impacts. Cocoa pod husk, which is generally considered as waste product after pod splitting, can also be used as organic fertiliser during cultivation [41]. Another option that could be considered is inter-cropping cocoa trees with other agroforestry crops like coconut.…”
Section: Improvement Options For Sustainabilitymentioning
confidence: 99%
“…Therefore, substituting the use of inorganic fertiliser with organic fertiliser would decrease the emissions and their related impacts. Cocoa pod husk, which is generally considered as waste product after pod splitting, can also be used as organic fertiliser during cultivation [41]. Another option that could be considered is inter-cropping cocoa trees with other agroforestry crops like coconut.…”
Section: Improvement Options For Sustainabilitymentioning
confidence: 99%
“…A lack of available labour also partly contributed to the use of children on cocoa farms (Barrientos et al 2008). Cocoa production in Ghana is also significantly challenged by pests and diseases such as mistletoe, capsid (insect), and black pod (fungus) (Bymolt et al 2018;Kongor et al 2017), which require timely spraying to mitigate their effects on crop losses estimated to reach about 30 per cent of annual cocoa production in some cases (Takyi et al 2019). Lack of access to inputs, especially fertilisers and agro-chemicals, also affects cocoa production.…”
Section: Challenges With the Cocoa Value Chain In Ghanamentioning
confidence: 99%
“…This core-periphery structure was significant in all four communities in this study. This type of centralized network structure was supported by findings in five communities a decade later; Nyantakyi-Frimpong et al (2019) showed positive and significant estimates of the 2-star parameter using ERGMs within the community networks, which suggests a centering of information ties on the most popular advisers. This is not uncommon as other work has shown that rural development programs and interventions may result in unequally distributed responsibilities and benefits, which could increase the centrality of involved individuals and potentially elevate core community members (Heß et al 2021).…”
Section: Agrobiodiversity Interventions and The Structure Of Informationsharing Networkmentioning
confidence: 56%
“…Drawing a link between networks and agrobiodiversity outcomes was possible only at the ego network level within our studies and it is important to emphasize that network mechanisms for community-level outcomes may be quite different. Indeed, Nyantakyi-Frimpong et al (2019) did not find any relationship between community-level outcomes and collective network structure that would parallel those at the individual level. Using ERGMs among five whole networks, there was no indication that larger, denser, or more clustered communities would have different levels of biomass from the adoption of agroforestry than communities that were smaller or sparser, or networks that have more evenly distributed relationships among the farmers.…”
Section: Scaling To the Community Level And The Role Of Environmental Spilloversmentioning
confidence: 94%